The good, the bad, and the Barbie : a doll's history and her impact on us - Stone, Tanya Lee. (Viking, 2010)
"Readers learn about Mattel Toys and the background behind Barbie's concept and development, how it was a solution for girls who wanted to imagine adult roles rather than just play mother, and details about inventor Ruth Handler."--Amazon.com.